Management Control Systems Practices in Nepalese Commercial Banks (The Batuk, 2025)
This study examines the impact of management control systems on the perceived performance of Nepalese commercial banks, focusing on key components such as budgeting, risk assessment, monitoring and supervision, information and communication, and the control environment. Employing a descriptive and causal research design, data were collected from 371 managers and employees across seven banks in Kathmandu using a structured questionnaire. The analysis, conducted through SPSS, utilized descriptive statistics, correlation, and regression models to assess the relationship between study variables. The findings reveal that a robust control environment and effective monitoring significantly enhance perceived performance, highlighting the critical role of management control systems components in achieving strategic alignment and operational efficiency within the sector. The study underscores the need for targeted managerial development and the integration of comprehensive management control systems frameworks to meet regulatory requirements and drive sustainable growth in Nepal's banking industry.